Study on Semiconductor Properties of Acetylide-Thiourea Fabricated onto Interdigitated Electrodes (Ides) Platform Towards Application In Gas Sensing Technology - Daud, Adibah Izzati; Khairul, Wan M.; Isa, M. I. N.; Wahid, Khairul Anuar Abdul (Makara Journal of Technology, 2017)
In the past few decades, the unique properties of acetylide and thiourea moieties individually have attracted great attention from researchers in various fields to be developed in numerous applications in advanced materials technology, especially as an active layer in gas sensing devices. The molecular systems of acetylide and thiourea provide a wide range of electronic properties as they possess rigid π-systems in their designated structures. In this study, a derivative of acetylide-thiourea featuring N-(4[4-aminophenyl] ethynyl benzonitrile)-N’-(4-ethyl benzoyl) thiourea (TCN) has been synthesised with the general formula of ArC(O)NHC(S)NHC≡C)Ar adopted the system of D-π-A for the significant development of conductive materials. The derivative consists of donating substituent characterised by typical spectroscopic techniques, such as infrared spectroscopy, UV-visible spectroscopy, and 1H and 13C Nuclear Magnetic Resonance. In turn, TCN was deposited onto interdigitated electrode (IDE) for the measurement of thin-film resistance. The resistance values of synthesised compound is caused the effect of donating substituent attached to the acetylide-thiourea, which indeed altered the conductivity performances of fabricated IDE substrate. In fact, the theoretical calculation also was carried out using Gaussian 09 to evaluate the relationship between experimental and theoretical analyses of acetylide-thiourea semiconductor properties in term of energy band gap and the sensing response to the selected analyte.